PERBANDINGAN ANALISA STRUKTUR DINDING GESER DAN SRPMK PADA GEDUNG 8 LANTAI - Ibrahim, Hasan; Rachman , Ari Putra; Tome, Nurhediyati (Universitas Bina Taruna Gorontalo, 2025)
The advancement of technology in society has significantly impacted urban development, particularly in Gorontalo Province, leading to increased mobility and activity among residents. This has resulted in the growth of residential buildings, places of worship, educational institutions, and shopping centers, with structures increasingly expanding vertically due to population growth. This study aims to compare the structural analysis of an 8-story reinforced concrete building using two lateral load-resisting systems: the Shear Wall System and the Special Moment-Resisting Frame (SMRF) System, analyzed using ETABS software. The findings reveal distinct structural behaviors between the two systems. The shear wall system exhibited a maximum inter-story drift of 38.367 mm in the x-direction and 7.840 mm in the y-direction, while the SMRF system showed 23.272 mm (x-direction) and 37.492 mm (y-direction). The most notable difference was observed in the y-direction, where the shear wall system demonstrated significantly lower drift values compared to the SMRF system. This indicates that the shear wall system provides better resistance to lateral displacements in high-rise buildings under similar conditions.